2015
DOI: 10.1108/ijpdlm-08-2014-0183
|View full text |Cite
|
Sign up to set email alerts
|

Moderating effect of environmental supply chain collaboration

Abstract: Purpose – The purpose of this paper is to explore how corporate environmental strategies, namely, environmental management strategy (EMS) and green product strategy (GPS), affect the competitiveness of a firm. In addition, this study investigates whether the environmental collaboration in supply chains (ECSC), namely, environmental collaboration with suppliers (ECS), and environmental collaboration with customers (ECC) moderate the environment-performance relationship. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 47 publications
(146 reference statements)
1
44
0
Order By: Relevance
“…It allows supporting suppliers and customers with resources and information to achieve their environmental goal. Studies (Chen et al, 2015;Vachon and Klassen, 2006) find that collaboration has positive impact on performance; few find positive relationship to economic; other find positive relationship to environment (Chen et al, 2015; and society or TBL (Blome et al, 2014;Sancha et al, 2016). Sancha et al (2016) assert suppliers' assessment improves buyer's social performance and collaborating with them improves suppliers' social performance.…”
Section: Sustainability and Collaborationmentioning
confidence: 99%
See 3 more Smart Citations
“…It allows supporting suppliers and customers with resources and information to achieve their environmental goal. Studies (Chen et al, 2015;Vachon and Klassen, 2006) find that collaboration has positive impact on performance; few find positive relationship to economic; other find positive relationship to environment (Chen et al, 2015; and society or TBL (Blome et al, 2014;Sancha et al, 2016). Sancha et al (2016) assert suppliers' assessment improves buyer's social performance and collaborating with them improves suppliers' social performance.…”
Section: Sustainability and Collaborationmentioning
confidence: 99%
“…Sancha et al (2016) assert suppliers' assessment improves buyer's social performance and collaborating with them improves suppliers' social performance. Both upstream and downstream collaboration is required for better performance towards sustainability (Chen et al, 2015).…”
Section: Sustainability and Collaborationmentioning
confidence: 99%
See 2 more Smart Citations
“…So, firms with proactive environmental strategies tend to voluntarily invest resources to achieve their goals [11]. A growing number of researchers have demonstrated that the process of implementation of strategy affects whether a well-developed strategy can achieve its goal [23,24]. Therefore, competitive approaches are essential for firms to implement their environmental strategies and achieve their goals [8].…”
Section: Proactive Environmental Strategy and Ghrmmentioning
confidence: 99%